Piperacillin pharmacokinetics and target attainment in children with cancer and fever: Can we optimize our dosing strategy?. Issue 6 (10th February 2019) - Maarbjerg, Sabine F.; Thorsted, Anders; Kristoffersson, Anders; Friberg, Lena E.; Nielsen, Elisabet I.; Wang, Mikala; Brock, Birgitte; Schrøder, Henrik
Abstract: Background: Data on piperacillin–tazobactam pharmacokinetics and optimal dosing in children with cancer and fever are limited. Our objective was to investigate piperacillin pharmacokinetics and the probability of target attainment (PTA) with standard intermittent administration (IA), and to simulate PTA in other dosing regimens. Procedure: This prospective pharmacokinetic study was conducted from April 2016 to January 2018. Children with cancer receiving empiric piperacillin–tazobactam to treat infections were included. Piperacillin–tazobactam 100 mg/kg was infused over 5 min every 8 hours (IA). An optimized sample schedule provided six blood samples per subject for piperacillin concentration determination. The evaluated targets included: (1) 100% time of free piperacillin concentration above the minimum inhibitory concentration ( f T > MIC) and (2) 50% f T > 4× MIC. MIC50 and MIC90 were defined based on an intrainstitutional MIC range. Results: A total of 482 piperacillin concentrations were obtained from 43 children (aged 1–18 years) during 89 fever episodes. Standard IA resulted in insufficient target attainment, with significant differences in piperacillin pharmacokinetics for different body weights. Median f T > MIC was 61.2%, 53.5%, and 36.3% for MIC50 (2.0 mg/L), MIC90 (4.0 mg/L), and breakpoint for Pseudomonas aeruginosa (16.0 mg/L), respectively. Correspondingly, the median f T > 4× MIC was 43%, 36.3%, and 20.1%. Simulations showed that only continuous infusion reached a PTA of 95% for MIC = 16.0 mg/L, while extended infusion lasting half of the dosing interval reached a PTA of 95% for MIC ≤ 8 mg/L. Conclusions: Our data revealed insufficient PTA with standard IA of piperacillin–tazobactam in children with cancer and fever. Alternative dosing strategies, preferably continuous infusion, are required to ensure adequate PTA.